At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Let's break down the problem step-by-step given the polynomials [tex]\(A, B,\)[/tex] and [tex]\(C\)[/tex]:
1. Define the polynomials:
[tex]\[ A = x^2 \][/tex]
[tex]\[ B = 3x + 2 \][/tex]
[tex]\[ C = x - 3 \][/tex]
2. Compute [tex]\(AB\)[/tex]:
[tex]\[ AB = A \cdot B = x^2 \cdot (3x + 2) \][/tex]
We distribute [tex]\(x^2\)[/tex] across each term inside the parentheses:
[tex]\[ AB = x^2 \cdot 3x + x^2 \cdot 2 = 3x^3 + 2x^2 \][/tex]
3. Compute [tex]\(C^2\)[/tex]:
[tex]\[ C^2 = (x - 3)^2 \][/tex]
We use the formula [tex]\((a - b)^2 = a^2 - 2ab + b^2\)[/tex]:
[tex]\[ C^2 = x^2 - 2 \cdot x \cdot 3 + 3^2 = x^2 - 6x + 9 \][/tex]
4. Subtract [tex]\(C^2\)[/tex] from [tex]\(AB\)[/tex]:
[tex]\[ AB - C^2 = (3x^3 + 2x^2) - (x^2 - 6x + 9) \][/tex]
Distribute the negative sign and combine like terms:
[tex]\[ AB - C^2 = 3x^3 + 2x^2 - x^2 + 6x - 9 \][/tex]
Simplify:
[tex]\[ AB - C^2 = 3x^3 + (2x^2 - x^2) + 6x - 9 = 3x^3 + x^2 + 6x - 9 \][/tex]
So, the expression [tex]\(AB - C^2\)[/tex] in simplest form is:
[tex]\[ 3x^3 + x^2 + 6x - 9 \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{3 x^3 + x^2 + 6 x - 9} \][/tex]
1. Define the polynomials:
[tex]\[ A = x^2 \][/tex]
[tex]\[ B = 3x + 2 \][/tex]
[tex]\[ C = x - 3 \][/tex]
2. Compute [tex]\(AB\)[/tex]:
[tex]\[ AB = A \cdot B = x^2 \cdot (3x + 2) \][/tex]
We distribute [tex]\(x^2\)[/tex] across each term inside the parentheses:
[tex]\[ AB = x^2 \cdot 3x + x^2 \cdot 2 = 3x^3 + 2x^2 \][/tex]
3. Compute [tex]\(C^2\)[/tex]:
[tex]\[ C^2 = (x - 3)^2 \][/tex]
We use the formula [tex]\((a - b)^2 = a^2 - 2ab + b^2\)[/tex]:
[tex]\[ C^2 = x^2 - 2 \cdot x \cdot 3 + 3^2 = x^2 - 6x + 9 \][/tex]
4. Subtract [tex]\(C^2\)[/tex] from [tex]\(AB\)[/tex]:
[tex]\[ AB - C^2 = (3x^3 + 2x^2) - (x^2 - 6x + 9) \][/tex]
Distribute the negative sign and combine like terms:
[tex]\[ AB - C^2 = 3x^3 + 2x^2 - x^2 + 6x - 9 \][/tex]
Simplify:
[tex]\[ AB - C^2 = 3x^3 + (2x^2 - x^2) + 6x - 9 = 3x^3 + x^2 + 6x - 9 \][/tex]
So, the expression [tex]\(AB - C^2\)[/tex] in simplest form is:
[tex]\[ 3x^3 + x^2 + 6x - 9 \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{3 x^3 + x^2 + 6 x - 9} \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.